Multiresponsive hybrid microgels and hollow capsules with a layered structure - Lapeyre, Véronique (Langmuir : the ACS journal of surfaces and colloids, 2009)
Various stimuli-responsive composite particles with a high control of their internal structure and their corresponding hollow capsules are synthesized and characterized by photon correlation spectroscopy, TEM, and AFM. Core-shell particles with a silica core and a thermoresponsive shell are obtained by polymerization of N-isopropylacrylamide (NIPAM) in the presence of silica seeds grafted with a high density of gamma-methacryloxypropyltrimethoxysilane (MPS). The influence of the synthesis conditions is studied. The shell thickness increases when the monomer concentration increases in a limited range where uniform composite particles with a single core are obtained. At constant monomer concentration, the shell thickness does not depend on the size of the silica seeds, but the presence of free unbound microgels is observed when the silica surface area decreases. A range of particle diameters and shell thicknesses is thus obtained, which can lead to the corresponding hollow capsules by exposure to hydrofluoric acid solution. The volume phase transition temperature of these materials can be easily tuned by replacing the NIPAM monomer by another N-alkylacrylamide derivative. However, the incorporation of comonomers such as acrylic acid (AA) and a phenylboronic acid (PBA) derivative inhibits the formation of core-shell structures. In order to get pH or glucose responsiveness, these functional groups can be incorporated in the outer shell of a core-double shell structure, with pNIPAM as intermediate shell. pH-responsive and glucose-responsive composite particles are obtained by this method with a high control of their internal structure